The Personal and the Political. The Child’s Body: Scientific Research and Public Policy - Diasio, Nicoletta; Sirota, Régine; Hamelin-Brabant, Louise (Enfances, Familles, Générations)

(untitled) (INRS-UCS, 2019)
Research Framework: This article examines the significance of the child’s body in contemporary societies and its influence on apparatus of scientific research and public intervention. Objectives: The objective is to show the politics of children’s bodies, health and lives, their historical manifestations between the late 18th and early 21st century and the way in which science, societal debates, and institutional and public policy contexts intersect. Methodology: This introduction is based on a multidisciplinary literature review that draws on sources in the fields of sociology, anthropology, history, and educational sciences. It is also the result of many years of research by the authors in collective research programs focused on children’s bodies and health. Results: Interest in the child’s body is not a recent phenomenon. It developed first in the crucible of the struggle against infant mortality, then in a biopolitics aimed at establishing or strengthening nation-states, and lastly in the medicalization of society and in changes in education and the family that put childhood at the heart of many public policies. The evolution of the status of the child, of being recognized as an actor and treated as sacred, combined with the concerns and uncertainties resulting from evolving family norms, have given rise to numerous programs of research and intervention. Conclusions: The politico-administrative and scientific spheres engage in dialogue on the subject of the child’s body, sometimes ignoring and sometimes reinforcing one other, drawing their legitimacy from different registers of normativity. Contribution: We show the specific forms of the “body politic” when it refers to children: its relationship to time; the practices of defining its entry into existence and its stages through life; the importance of transitions; the competition and normative conflicts between various actors; conditions of existence and power relations that segment childhoods and produce unequal lives. Knowledge and expertise have become a means of legitimizing the implementation of public actions with regard to childhood, although their flow between the scientific world and political arenas is not always linear or easy.